1993
DOI: 10.1111/j.1471-4159.1993.tb03172.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐Mediated Calcium Response and Inositol 1,4,5‐Trisphosphate Release in Neuroblastoma‐Glioma Hybrid Cells (NG108‐15): Cross Talk with ATP and Bradykinin

Abstract: J. Neurochem. 60,[454][455][456][457][458][459][460].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
3
1
1
Order By: Relevance
“…Our results are compatible with previous reports on ET stimulation of PIs turnover in rat neuroblastoma-glioma hybrid cells (Chau et al, 1993), glial cells (Marsault et al, 1990), in cerebellar granule and glioma cells , and in brain structures such as the subfornical organ and median eminence (Garrido and Israel, 1994). Our findings differ from the previous study of bovine chromaffin ETs-stimulated cGMP production (right) in rat adrenal medulla.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results are compatible with previous reports on ET stimulation of PIs turnover in rat neuroblastoma-glioma hybrid cells (Chau et al, 1993), glial cells (Marsault et al, 1990), in cerebellar granule and glioma cells , and in brain structures such as the subfornical organ and median eminence (Garrido and Israel, 1994). Our findings differ from the previous study of bovine chromaffin ETs-stimulated cGMP production (right) in rat adrenal medulla.…”
Section: Discussioncontrasting
confidence: 56%
“…The high capacity of bradykinin to induce desensitization processes is emphasised by the finding that bradykinin can also very efficiently induce heterologous desensitization. Recently it was reported that bradykinin completely abolishes the endothelin-induced cytosolic [Ca"] rise in NG 108-15 cells (Chau et al, 1993).…”
Section: Properties Of the Nuclear [Ca2+] Risementioning
confidence: 99%
“…For example, ET facilitates the release of intracellular Ca2" with a slow equilibrium with the extracellular cation in contrast to the Ca2" pool mobilized by ATP (Figure 7a). In this connection, Chau et al (1993) recently suggested that both ET and ATP hydrolyze a separate pool of polyphosphoinositides in neuroblastoma-glioma hybrid cells resulting in additive responses due to the release of separate pools of Ca2+. Alternatively, an ETA membrane receptor may 'cross-talk' with a P2.-purinoceptor increasing its affinity and/or modifying its ionophore function ( Figure 7b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ET facilitates the release of intracellular Ca2" with a slow equilibrium with the extracellular cation in contrast to the Ca2" pool mobilized by ATP (Figure 7a). In this connection, Chau et al (1993) creasing its affinity or altering the kinetics of its ionophore function (Figure 7c). With regard to the increase in bladder tension caused by the ETs, the ETA receptor involved could be coupled to a calcium channel mainly dependent on the influx of extracellular Ca2+ (Figure 7).…”
Section: Discussionmentioning
confidence: 99%